Fabrication of biphasic cartilage-bone integrated scaffolds based on tissue-specific photo-crosslinkable acellular matrix hydrogels. (15th December 2022) - Hua, Yujie; Huo, Yingying; Bai, Baoshuai; Hao, Junxiang; Hu, Guanhuai; Ci, Zheng; Wu, Xiaodi; Yu, Mengyuan; Wang, Xin; Chen, Hong; Ren, Wenjie; Zhang, Yixin; et al.
Abstract: The fabrication of biphasic cartilage-bone integrated scaffolds is an attractive alternative for osteochondral repair but has proven to be extremely challenging. Existing three-dimensional (3D) scaffolds are insufficient to accurately biomimic the biphasic cartilage-bone integrated microenvironment. Currently, photo-crosslinkable hydrogels based on tissue-specific decellularized extracellular matrix (dECM) have been considered as an important technique to fabricate biomimetic scaffolds, but so far there has been no breakthrough in the photo-crosslinkable hydrogel scaffolds with biphasic cartilage-bone biomimetic microenvironment. Here, we report a novel strategy for the preparation of biomimetic cartilage-bone integrated scaffolds based on photo-crosslinkable cartilage/bone-derived dECM hydrogels, which are able to reconstruct biphasic cartilage-bone biomimetic microenvironment. The biphasic cartilage-bone integrated scaffolds provided a 3D microenvironment for osteochondral regeneration. The cartilage biomimetic scaffolds, consisting of cartilage-derived dECM hydrogels, efficiently regulated chondrogenesis of bone marrow mesenchymal stem cells (BMSCs). The bone biomimetic scaffolds, composed of cartilage/bone-derived dECM hydrogels, first regulated chondrogenesis of BMSCs, followed by endochondral ossification over time. Taken together, the biphasic cartilage-bone integrated tissue could be successfully reconstructed by subcutaneous culture based on cartilage-bone bilayered structural design. Furthermore, the biphasic cartilage-bone biomimetic scaffolds (cell-free) achieved satisfactory cartilage-bone integrated regeneration in the osteochondral defects of rabbits' knee joints.